Potential Investigation of Membrane Energy Recovery Ventilators for the Management of Building Air-Conditioning Loads - Hadeed Ashraf; Muhammad Sultan; Uzair Sajjad; Muhammad Wakil Shahzad; Muhammad Farooq; Sobhy M. Ibrahim; Muhammad Usman Khan; Muhammad Ahmad Jamil (Energies, 2022)
The present study provides insights into the energy-saving potential of a membrane energy recovery ventilator (ERV) for the management of building air-conditioning loads. This study explores direct (DEC), Maisotsenko cycle (MEC) evaporative cooling, and vapor compression (VAC) systems with ERV. Therefore, this study aims to explore possible air-conditioning options in terms of temperature, relative humidity, human thermal comfort, wet bulb effectiveness, energy saving potential, and CO2 emissions. Eight different combinations of the above-mentioned systems are proposed in this study i.e., DEC, MEC, VAC, MEC-VAC, and their possible combinations with and without ERVs. A building was modeled in DesignBuilder and simulated in EnergyPlus. The MEC-VAC system with ERV achieved the highest temperature gradient, wet bulb effectiveness, energy-saving potential, optimum relative humidity, and relatively lower CO2 emissions i.e., 19.7 °C, 2.2, 49%, 48%, and 499.2 kgCO2/kWh, respectively. Thus, this study concludes the hybrid MEC-VAC system with ERV the optimum system for the management of building air-conditioning loads.